Here is your life - Nordgren, Erik 1913-1992 (The Criterion collection, 2015)
"This mesmerizing debut by the great Swedish director Jan Troell is an epic bildungsroman and a multilayered representation of early twentieth-century Sweden. Based on a series of autobiographical novels by Nobel Prize winner Eyvind Johnson, "Here Is Your Life" follows a working-class boy’s development, from naive teenager to intellectually curious young adult, from logger to movie projectionist to politically engaged man of the people -all set against the backdrop of a slowly industrializing rural landscape. With its mix of modernist visual ingenuity and elegantly structured storytelling, this enchanting film-presented here in its original nearly three-hour cut is a reminder that Troell is one of European cinema’s finest and most sensitive illuminators of the human condition." [criterion.com]
Original: Schweden 1966
Bildformat 1.66:1
Two-DVD special edition features: new 2K digital restoration ; new introduction by filmmaker Mike Leigh ; new conversation between director Jan Troell and film historian Peter Cowie ; new interviews with actor Eddie Axberg and producer and coscreenwriter Bengt Forslund ; "Interlude in the Marshland", a 1965 short film by Troell, starring Max von Sydow ; new english subtitle translation ; plus: an essay by film scholar Mark Le Fanu
Keywords: Film; DVD-Video